The guided fire from within: intratumoral administration of mRNA-based vaccines to mobilize memory immunity and direct immune responses against pathogen to target solid tumors - Renhao Li; Jing-Chu Hu; Li Rong; Yige He; Xiaolei Wang; Xuansheng Lin; Wenjun Li; Yangfan Wu; Chaiyaporn Kuwentrai; Canhui Su; Thomas Yau; Ivan Fan-Ngai Hung; et al. (Cell Discovery)
Abstract We investigated a novel cancer immunotherapy strategy that effectively suppresses tumor growth in multiple solid tumor models and significantly extends the lifespan of tumor-bearing mice by introducing pathogen antigens into tumors via mRNA-lipid nanoparticles. The pre-existing immunity against the pathogen antigen can significantly enhance the efficacy of this approach. In mice previously immunized with BNT162b2, an mRNA-based COVID-19 vaccine encoding the spike protein of the SARS-CoV-2 virus, intratumoral injections of the same vaccine efficiently tagged the tumor cells with mRNA-expressed spike protein. This action rapidly mobilized the pre-existing memory immunity against SARS-CoV-2 to kill the cancer cells displaying the spike protein, while concurrently reprogramming the tumor microenvironment (TME) by attracting immune cells. The partial elimination of tumor cells in a normalized TME further triggered extensive tumor antigen-specific T cell responses through antigen spreading, eventually resulting in potent and systemic tumor-targeting immune responses. Moreover, combining BNT162b2 treatment with anti-PD-L1 therapy yielded a more substantial therapeutic impact, even in “cold tumor” types that are typically less responsive to treatment. Given that the majority of the global population has acquired memory immunity against various pathogens through infection or vaccination, we believe that, in addition to utilizing the widely held immune memory against SARS-CoV-2 via COVID-19 vaccine, mRNA vaccines against other pathogens, such as Hepatitis B Virus (HBV), Common Human Coronaviruses (HCoVs), and the influenza virus, could be rapidly transitioned into clinical use and holds great promise in treating different types of cancer. The extensive selection of pathogen antigens expands therapeutic opportunities and may also overcome potential drug resistance.